Hydrogen diffusivity and tensile properties degradation in SLMed Inconel 718. Issue 1 (January 2022) - Aiello, F; Beghini, M; Bertini, L; Macoretta, G; Monelli, B D; Valentini, R
Abstract: Besides elevated temperature applications, Inconel 718 is widely chosen for components subjected to heavy loads operating in aggressive environments, which can promote the production of hydrogen on the metal surface. Selective Laser Melting (SLM) is an emerging technology for the production of structural components in Inconel 718 or Inconel 625 alloys, allowing to create functionally optimized shapes and overcome the traditional manufacturing limitations. However, the SLM process introduces a peculiar microstructure and severe residual stresses that can affect hydrogen migration and accumulation. While the mechanical properties were deeply investigated in recent years, the resistance of SLMed Inconel 718 to the Hydrogen Embrittlement (HE) is still an open issue. The present work deals with a preliminary assessment of the hydrogen embrittlement susceptibility of the SLMed In718 in the as-built condition. Slow strain rate tests were carried out on unnotched specimens that were pre-charged by electrochemical cathodic charging. Fractographic analyses, carried out with a Scanning Electron Microscope (SEM), were used to identify the effects produced by the hydrogen intake on the material microstructure. The material resulted to be susceptible to hydrogen embrittlement, featuring a significant ductility reduction in presence of extremely elevated hydrogen concentrations. The hydrogen content was measured by employing the Hot Extraction Method (HEM), for each mechanical test. Due to a low diffusivity value, hydrogen penetrates only within a thin external layer of the specimen. Therefore, to identify the concentration profile, the effective hydrogen diffusion coefficient was identified and the hydrogen diffusion was simulated using Fick's equation. The loss in mechanical resistance was then correlated to the hydrogen concentration near the fracture onset.